2016
DOI: 10.1016/j.phrs.2015.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the efficacy of melatonin to curtail benzodiazepine/Z drug abuse

Abstract: The abuse of benzodiazepine (BZP) and Z drugs has become, due to the tolerance and dependence they produce, a serious public health problem. Thirty years ago, we demonstrated in experimental animals the interaction of melatonin with central BZD receptors, and in 1997 we published the first series of elderly patients who reduced BZP consumption after melatonin treatment. Almost every single neuron in the hypothalamic suprachiasmatic nuclei (SCN), the central pacemaker of the circadian system, contains γ-aminobu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 129 publications
(143 reference statements)
0
15
0
2
Order By: Relevance
“…Its potentiality in treating sleep disturbances is relevant because the sleep-promoting compounds that are usually prescribed in cancer patients, like benzodiazepines and related Z drugs, have many adverse effects, such as next-day hangover, dependence and impairment of cognition. Indeed, a number of studies point out to a beneficial effect of melatonin in a wide variety of sleep disorders [180] and melatonin is increasingly recognized as an effective medication to stop benzodiazepine/Z drug abuse in patients [181]. Melatonin has been used for improving sleep in patients with insomnia mainly because it does not cause hangover or show any addictive potential.…”
Section: Levels Of Amt6s In 12-h Overnight Urine Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…Its potentiality in treating sleep disturbances is relevant because the sleep-promoting compounds that are usually prescribed in cancer patients, like benzodiazepines and related Z drugs, have many adverse effects, such as next-day hangover, dependence and impairment of cognition. Indeed, a number of studies point out to a beneficial effect of melatonin in a wide variety of sleep disorders [180] and melatonin is increasingly recognized as an effective medication to stop benzodiazepine/Z drug abuse in patients [181]. Melatonin has been used for improving sleep in patients with insomnia mainly because it does not cause hangover or show any addictive potential.…”
Section: Levels Of Amt6s In 12-h Overnight Urine Samplesmentioning
confidence: 99%
“…MT 1 and MT 2 receptors also appear to be involved in sedating and anxiolytic effects of melatonergic drugs which have been linked to a facilitatory role of melatonin on γ-aminobutyric acid transmission [194]. This antiexcitatory action of melatonin may underlie the anxiolytic, antihyperalgesic and antinociceptive effects of melatonergic agents, all them of potential application in cancer patients [4,181]. In a doubleblind, placebo-controlled study of 54 women undergoing surgery for breast cancer and receiving 6 mg of melatonin or placebo for 3 months, No significant association was found between aMT6s and breast cancer risk, either overall (for highest third vs. lowest, multivariable-adjusted odds ratio = 0.90, 95% confidence interval: 0.61, 1.33) or by menopausal status.…”
Section: Levels Of Amt6s In 12-h Overnight Urine Samplesmentioning
confidence: 99%
“…Tolerance, dependence and adverse effects associated with the abuse of benzodiazepines and Z-drugs have become a serious public health issue [7] [8] [9].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin competes with BZD and Z drugs at their site of action. A facilitator role of melatonin on GABA neurotransmission explains the anxiolytic, antihyperalgesic and antinociceptive effects of melatonergic agents (Cardinali et al, 2016). Several clinical studies now support the efficacy of melatonin to reduce BZD use in chronically treated patients (Baandrup et al, 2016a, Baandrup et al, 2016b, Cardinali et al, 2016.…”
Section: Melatonin and Bzd Interactionmentioning
confidence: 99%
“…A facilitator role of melatonin on GABA neurotransmission explains the anxiolytic, antihyperalgesic and antinociceptive effects of melatonergic agents (Cardinali et al, 2016). Several clinical studies now support the efficacy of melatonin to reduce BZD use in chronically treated patients (Baandrup et al, 2016a, Baandrup et al, 2016b, Cardinali et al, 2016. In a pharmaco-epidemiologic study aimed to evaluate the impact of anti-BZD / Z drugs campaigns and the availability of alternative pharmacotherapy (melatonin) on the consumption of BZD and Z drugs in several European countries, the results indicated that campaigns failed unless they were associated with the availability of melatonin in the market (Clay et al, 2013).…”
Section: Melatonin and Bzd Interactionmentioning
confidence: 99%